Influence of IL-β, IL-1RN, and TNF-α variants on the risk of acetylsalicylic acid-induced upper gastrointestinal bleeding: a case-control study - Forgerini, Marcela [UNESP] (2024)
OBJECTIVE: Forgerini et al. investigated the role of seven genetic variants in the risk of upper gastrointestinal bleeding as an adverse drug reaction. In 289 participants (50 cases and 189 controls), the presence of seven variants in the IL-1β, IL-1RN, and TNF-α genes was not associated with susceptibility to acetylsalicylic acid-induced upper gastrointestinal bleeding. The use of acetylsalicylic acid, even in low doses, may be associated with the onset of upper gastrointestinal bleeding as an idiosyncratic response. Considering the role of the genetic background in inter-individual responses to pharmacotherapy, we aimed to investigate the role of seven variants in the TNF-α, IL-β, and IL-1RN genes in association with the risk of upper gastrointestinal bleeding in users of low-dose acetylsalicylic acid for the prevention of cardiovascular events. METHODS: A case-control study was conducted in a Brazilian hospital complex. The Case Group comprised patients diagnosed with upper gastrointestinal bleeding who were administered a low dose of acetylsalicylic acid (n=50). Two Control Groups were recruited: 1) low-dose acetylsalicylic acid users without gastrointestinal complaints and under the supervision of a cardiologist (n=50) and 2) healthy controls (n=189). Sociodemographic, clinical, pharmacotherapeutic, and lifestyle data were recorded through face-to-face interviews. Genomic DNA from all participants was genotyped for rs16944 and rs1143634 (IL-β gene), rs4251961 (IL-1RN gene), and rs1799964, rs1799724, rs361525, and rs1800629 (TNF-α gene). RESULTS: No significant difference was noted in the genotypic frequencies of TNF-α, IL-β, and IL-1RN variants between the Case and Control Groups of low-dose acetylsalicylic acid users (p>0.05). The frequency of rs1800629 genotypes (TNF-α gene) differed significantly between the Case Group and healthy controls (p=0.003). None of the evaluated variants were associated with a risk of upper gastrointestinal bleeding. CONCLUSION: This study aimed to explore pharmacogenomics biomarkers in low-dose acetylsalicylic acid users. Our data suggest that the presence of IL-1β, IL-1RN, and TNF-α variants was not associated with an increased risk of upper gastrointestinal bleeding.